DESIGN AND FABRICATION OF POLYMER-CERAMIC COMPOSITE HIP PROSTHESIS - S BAG; S PAL (International Journal of Pharma and Bio Sciences, 2014)
A composite hip prosthesis (CHP) made from alumina reinforced ultra high molecular weight polyethylene (UHMWPE) was designed and manufactured. The main objective of the study was to fabricate the composite hip prosthesis which would be an ideal replacement of metallic one as bone is a composite material consisting of collagen fibre matrix and embedded hydroxyapatite mineral. With this idea we developed a composite material using UHMWPE (Ultra High Molecular Weight Polyethylene ) and alumina ceramic in various percentages whose properties are similar to that of bone. Hip prosthesis mould was designed and developed as per standard size and shape of Austein Moore metallic hip prosthesis and the alumina reinforced UHMWPE (GUR 4020) composite hip prosthesis was fabricated in the 3 piece hip mould using compression moulding technique. After fabrication, a static compression test was carried out to observe the deflection under loading condition. From the graph, it was calculated that the deflection without any cement was 30% higher than that with bone cement fixation. This type of composite hip prosthesis may be used in patient with lesser body weight.